Strategia przetrwania. Brygada śmierci Leona Weliczkera - Przymuszała, Beata (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
This article discusses the testimony of Leon Weliczker (The Brigade of Death), who was at the Sonderkommando in the Janowska camp. Describing the daily focus on the removal of corpses Weliczker simultaneously reveals his ways of survival. Discourse on trauma focuses on its subsequent impact, in the case of the analyzed text we are dealing with an attempt to record the traumatic state. Using the psychological context, the author shows how Weliczker tried to minimize the impact of trauma using various mechanisms of controlling and displacing emotions.